Development and progression association of various ophthalmic pathologies with the gut microbiome state (literature review) - G.N. Rezbaeva; A.E. Babushkin; O.I. Orenburkina; I.A. Gimranova (РМЖ "Клиническая офтальмология")
G.N. Rezbaeva1, A.E. Babushkin2, O.I. Orenburkina1, I.A. Gimranova3 1All-Russian Center for Eye and Plastic Surgery of the Bashkir State Medical University, Ufa, Russian Federation 2Ufa Research Institute of Eye Diseases of the Bashkir State Medical University, Ufa, Russian Federation 3Bashkir State Medical University, Ufa, Russian Federation Study results presented in this review concern the role of changes in the intestinal microbiota composition (the so-called gut microbiota dysbiosis) in the development and/or progression of various eye diseases. Nowadays, about 1150 species of microorganisms that can colonize the GIT have been identified, but no more than 20–30% of them can be cultivated. A huge study breakthrough of the gut microbiota species composition in a healthy person, as well as in persons with various pathologies, was obtained after a technique development for DNA sequencing. Modern researches focus on studying the effect of changes in the gut microbiome on human health, including his eyes. This suggests the potential use of this indicator as a non-invasive biomarker during differential diagnosis, as well as its introduction for ophthalmic therapy purposes. In particular, the association between the gut microbiota and the eyes can serve as a basis for the technique development aimed at the treatment of a number of eye diseases. For instance, dry eye syndrome, especially chronic progressive ophthalmic pathology, such as diabetic retinopathy, glaucoma, age-related macular degeneration, etc. Keywords: microbiome, gut microbiota dysbiosis, association with eye diseases, development of treatment techniques. For citation: Rezbaeva G.N., Babushkin A.E., Orenburkina O.I., Gimranova I.A. Development and progression association of various ophthalmic pathologies with the gut microbiome state (literature review). Russian Journal of Clinical Ophthalmology. 2023;23(4):219–224 (in Russ.). DOI: 10.32364/2311-7729-2023-23-4-8.